2018
DOI: 10.1519/jsc.0000000000002172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jaw Clenching and Jaw Alignment Mouthpiece Use on Force Production During Vertical Jump and Isometric Clean Pull

Abstract: Allen, CR, Fu, Y-C, Cazas-Moreno, V, Valliant, MW, Gdovin, JR, Williams, CC, and Garner, JC. Effects of jaw clenching and jaw alignment mouthpiece use on force production during vertical jump and isometric clean pull. J Strength Cond Res 32(1): 237-243, 2018-This study examined the effects of jaw clenching, a self-adapted, jaw-repositioning mouthpiece on force production during maximum countermovement vertical jump and maximum isometric midthigh clean pull assessments in an attempt to determine any ergogenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 14 publications
1
43
0
Order By: Relevance
“…To control for jaw musculature activation during the jaw relaxed condition, participants were instructed to breathe through pursed lips for the duration of each vertical jump and grip strength assessment trial. Pursed lip breathing is believed to limit jaw musculature activation and is consistent with previously published research (Allen et al, 2016;Allen et al, 2018;Ebben et al, 2010a;Garceau et al, 2012). Following the completion of each assessment trial, participants were asked whether they maintained the required breathing pattern and whether their jaw muscula-ture activation was maximal or remained relaxed.…”
Section: Participants and Designsupporting
confidence: 89%
See 3 more Smart Citations
“…To control for jaw musculature activation during the jaw relaxed condition, participants were instructed to breathe through pursed lips for the duration of each vertical jump and grip strength assessment trial. Pursed lip breathing is believed to limit jaw musculature activation and is consistent with previously published research (Allen et al, 2016;Allen et al, 2018;Ebben et al, 2010a;Garceau et al, 2012). Following the completion of each assessment trial, participants were asked whether they maintained the required breathing pattern and whether their jaw muscula-ture activation was maximal or remained relaxed.…”
Section: Participants and Designsupporting
confidence: 89%
“…Hiroshi (2003) demonstrated that peak force and rate of force development were significantly improved when jaw clenching was employed just before and during dominant handgrip strength assessment in male participants. Peak force and rate of force development were also improved during maximal isometric clean pull performance (Allen et al, 2018). Additionally, Busca et al (2016), while investigating the effects of jaw clenching and bite-aligning mouthpieces on strength, reported a significant improvement in dominant handgrip strength performance when male participants maximally clenched the jaw compared to not clenching.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In dentate individuals, jaw-repositioning devices have been shown to improve muscular power (Allen et al, 2018). This differs from strength in that it requires a rapid neuromuscular response.…”
Section: Occlusion and Forcementioning
confidence: 99%